Mastitis in rabbits caused by Pasteurella multocida - Rezende, Ana Margarida Langenegger; Marques, Lúcia Maria Queiroz; Neves, Ismar Pereira; Coelho, Nilton Martins; Gomes, Walter Vígio (Pesquisa Agropecuaria Brasileira, 2014)
Pasteurellosis was diagnosed in 31.6 per cent of 455 rabbits submitted for post-mortem examination from different breeders of the Município de Itaguaí, State of Rio de Janeiro. In the same rabbits, 17 cases of chronic mastitis with abscess formation caused by Pasteurella multocida were observed. Clinically, there were nodules and an assymmetric increase in size of one or several mammary glands. Post-mortem examination revealed increased consistency and the presence of dense white-yellowish pus within the affected glands. Histopathological examination revealed chronic inflammatory changes with abscess formation. Pure cultures of P. multocida were isolated from the pus by bacteriologic examination.